The threat of unsolicited sessions in the 3GPP IP multimedia subsystem. - Waiting, David (IEEE Communications magazine)
Unsolicited emails distributed by marketers and fraudsters are a growing burden on Internet users. It is expected that with the introduction of low-cost next-generation networks, such as the IP multimedia subsystem, these unsolicited communications will migrate from email and move to voice, video, and instant messaging sessions. Unsolicited voice and video calls are highly disruptive, causing frustration to end users, and they are wasteful of network resources. These communications also may involve fraud, phishing, or the propagation of offensive material. This article highlights the scale of this inevitable problem and proposes mechanisms to enable users to filter their incoming multimedia sessions, such that only legitimate calls are received. This is achieved in a variety of ways including call-pattern analysis, statistical filtering, blacklists, whitelists, and challenge-response mechanisms.